Implementation of Domestic Violence Prevention and Response Policy in Bekasi Regency - Ismamati, Yulia; Rahayu, Susi Dian (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
Domestic violence experienced by women in Indonesia is increasingly prevalent every year. It is one of the highest cases of overall violence against women. Bekasi Regency is one of the areas with high cases of domestic violence. From 2018 to 2022, there were 169 cases of domestic violence reported to the Bekasi Regency Women's and Children's Empowerment and Protection Service (DPPPA). This study aims to analyze the implementation of policies related to the prevention and protection of women against domestic violence in Bekasi Regency. This research uses the theory of policy implementation from Van Meter and Van Horn. This research uses a qualitative method using a descriptive analysis approach. The results of this study indicate that the implementation of Bekasi Regency Regional Regulation Number 5 of 2020 concerning the protection of women against domestic violence in Bekasi Regency has not been implemented. Because, since the enactment of the regulation, cases of violence against women have increased every year, especially the number of cases of domestic violence in Bekasi Regency. This is due to several factors, including weak regulations related to the prevention and protection of women against domestic violence, victims who do not dare to speak up, efforts to resolve domestic violence cases, which are sometimes only resolved within the family, and other external factors such as social and economic factors, which contribute to the higher rate of domestic violence in Bekasi Regency.